Bessarion's treasure editing, translating and interpreting bessarion's literary heritage - Annick, Peters-Custot; Eva, Del Soldato; Fabio, Pagani; Frederick, Lauritzen; Georgios, Steiris; John A., Demetracopoulos; John, Monfasani; Panagiotis Ch., Athanasopoulos (Byzantinisches Archiv - Series Philosophica, 2021)
The importance of Bessarion's contribution to the history of Byzantine and Renaissance philosophy and culture during the 15th century is beyond dispute. However, an adequate appreciation of his contribution still remains a desideratum of scholarly research. One serious impediment to scholarly progress is the fact that the critical edition of his main philosophical work "In Calumniatorem Platonis" is incomplete and that this work has not been translated in its entirety into any modern language yet. Same can be stated about several minor but equally important treatises on literary, theological and philosophical subjects. This makes editing, translating and interpreting his literary, religious and philosophical works a scholarly priority. Papers assembled in this volume highlight a number of philological, philosophical and historical aspects that are crucial to our understanding of Bessarion's role in the history of European civilization and to setting the directions of future research in this field